2019
DOI: 10.21203/rs.2.13659/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Application of Enhanced Recovery after Surgery for Upper Gastrointestinal Surgery: Meta-Analysis

Abstract: Background: Although enhanced recovery after surgery (ERAS) has made great progress in the field of surgery, the guidelines point to the lack of high-quality evidence in upper gastrointestinal surgery. Methods : Randomized controlled trials in four electronic databases that involved ERAS protocols for upper gastrointestinal surgery were searched through December 12, 2018. The primary endpoints were lung infection, urinary tract infection, surgical site infection, postoperative anastomotic leakage and ileus. Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…A meta-analysis found the ERAS protocol in gastric cancer to be associated with a significant reduction in LOS (23). Mean LOS was reported to range from 5.4 to 14.1 days (19). Our study found a mean LOS after radical gastrectomy of 6.9 days, which is comparable to that previous study.…”
Section: Discussion Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…A meta-analysis found the ERAS protocol in gastric cancer to be associated with a significant reduction in LOS (23). Mean LOS was reported to range from 5.4 to 14.1 days (19). Our study found a mean LOS after radical gastrectomy of 6.9 days, which is comparable to that previous study.…”
Section: Discussion Discussionsupporting
confidence: 79%
“…Previous study reported the benefit of ERAS protocol for reducing hospital LOS (19). Our study found the LOS in ERAS to be significantly shorter than in CC.…”
Section: Discussion Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…50 However, in 2020, a meta-analysis comprising 1830 patients showed that ERAS may increase the risk of POI. 51 Our study shows that paralytic ileus hospitalizations increased from 2001 to 2011. Even if these protocols were applied during the study period, NIS database does not have separate ICD-9 codes to identify such them.…”
Section: Discussionmentioning
confidence: 56%